Development and validation of a RP- HPLC method for the quantitation studies of praziquantel and pyrantel pamoate - Elena Gabriela Oltean (Medicamentul Veterinar)
An isocratic high-performance liquid chromatography (HPLC) procedure was developed for quantitative determination of praziquantel and pyrantel pamoate in tablet dosage forms of TOTAL. HPLC separation wascarried out by reversed phase chromatography Betasil C18 (250 mm x 4,6mm i.d.; 5 5m particle size), held at 25°C respective Kromasil 60-5SIL. (250 mm x 4,6 mm i.d.; 5 5m particle size), held at 25°C. The mobile phase consisted of acetonitrile/distilled water (60/40v/v), run at flow rate of 1 mL/min and with UV detection at 210nm, respective acetonitrile/ 0,1% phosphoric acid aq. (60/40 v/v), run at flow rate of 1 mL/ min and with UV detection at 240 nm. Method validation investigated parameters such as linearity (r2=0,9999), range, precision, accuracy and specificity. The described method can be successfully applied for the analysis of TOTAL tablets.